1997
DOI: 10.1111/j.1745-9125.1997.tb00880.x
|View full text |Cite
|
Sign up to set email alerts
|

A Test of the Black Subculture of Violence Thesis: A Research Note*

Abstract: We use data from the General Social Survey (1983 to 1991) to test Wolfgang and Ferracuti's hypothesis that violent values are widespread among African‐Americans. Contrary to the expectations of the black subculture of violence thesis, our analyses indicate that white males are significantly more likely than blacks to express violent tendencies in defensive situations and that there is no significant difference between white and black males in offensive situations, ceteris paribus. Thus, we have rejected, withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 28 publications
1
28
1
Order By: Relevance
“…The strongest statistically significant effect in both models is the percent of the population black, which is consistent with the findings of Cao, Adams, & Jensen (1997) and Covington (1999), both of which found significant positive correlations between concentrations of African-Americans in population and homicide rates. The next strongest effect in both models is ALCOHOL, which is consistent with Parker (1995) and Pernanen (1991), both of whom find that alcohol availability exerts especially robust effects on homicide rates.…”
Section: Discussionsupporting
confidence: 89%
“…The strongest statistically significant effect in both models is the percent of the population black, which is consistent with the findings of Cao, Adams, & Jensen (1997) and Covington (1999), both of which found significant positive correlations between concentrations of African-Americans in population and homicide rates. The next strongest effect in both models is ALCOHOL, which is consistent with Parker (1995) and Pernanen (1991), both of whom find that alcohol availability exerts especially robust effects on homicide rates.…”
Section: Discussionsupporting
confidence: 89%
“…The evidence is unclear as to whether blacks and whites differ in their attitudes toward violence (e.g., Blumenthal 1972;Cao et al 1997;Erlanger 1974;Markowitz and Felson 1998;Rossi et al 1974). On the other hand, race differences in violence have been observed at colleges and prisons where blacks and whites are living in similar circumstances (e.g., Harer and Steffensmeier 1996;Volkwein et al 1995).…”
Section: Race and Honor Culturesmentioning
confidence: 97%
“…They argue that there are regional differences in gun culture, not in honour culture as posited by Cohen, because while gun homicide rates are differentiated, homicide rates without guns are not. Cao et al (1997) suggested that gender and childhood socialization into gun culture are significantly related to protective and general (or sport) firearm possession. In contrast only protective firearm ownership appears to be linked to crime related factors.…”
Section: Introductionmentioning
confidence: 98%